Experience with a third-generation parathyroid hormone assay (BIO-PTH) in the diagnosis of primary hyperparathyroidism in a Brazilian population - Bonanséa,Teresa Cristina P. (2016)
ABSTRACT Objective To evaluate the usefulness of a third-generation PTH assay in the diagnosis of primary hyperparathyroidism (PHPT). Subjects and methods Forty-one PHPT patients (4 men and 37 women) with 61.2 ± 10.9 (mean ± SD) years, were studied and had PTH levels measured with two different methods using the same immunochemiluminescent assay plataform (Elecsys 2010 System, Roche). We compared a second-generation assay (I-PTH) with a third-generation PTH assay (Bio-PTH). Two populations of 423 and 120 healthy adults with serum 25OHD levels above 25 ng/mL were used to define normal values in the I-PTH and Bio-PTH assays respectively. Results Normal PTH values based in the healthy adults population were 24.2-78.0 pg/mL for the I-PTH assay and 19.9-58.5 pg/mL for Bio-PTH assay. In PHPT patients, PTH values ranged from 67 to 553 pg/mL (median: 168 pg/mL) using the I-PTH assay and from 55 to 328 pg/mL (median: 111 pg/mL) using the Bio-PTH assay. Results obtained with the Bio-PTH assay were significantly lower (p < 0.0001, Wilcoxon). In general I-PTH and Bio-PTH showed highly significant correlation (r = 0.952, p < 0.0001). Passing–Bablok analysis gave a regression equation of Bio PTH = 13.44 + 0.59 x intact PTH. PHPT patients had 25OHD levels ranging from 4 to 36 ng/mL (mean 16.2 ng/mL); 35 subjects (85.3%) had values bellow 25 ng/mL. Conclusion Our results demonstrate that both second and third generation PTH methods are strongly correlated in PHPT patients and control subjects. Lower results with Bio-PTH tests are expected in function of the assay specificity determined by the amino-terminal antibody used.